(untitled) (Research, Society and Development, 2020)
Rural work is considered vulnerable to acidentes due to the amount and diversity of risks involved. This study aimed to describe accidents with rural workers, from case series to the cases evolution, in municipalities covered by Reference Center for Occupational Health (CEREST) of Sobral - Ceará, Brazil. This is an epidemiological, descriptive and retrospective study, developed with 509 cases of rural work accidents, reported by Notifiable Diseases Information System (SINAN), between January 2009 and December 2013. Accidents was more frequently at the contracted’s premises (50.7% - 258), most of which were classified as typical accidents (77.4 - 494). There was a predominance of male workers (90.5% - 461), aged between 20 and 59 years. The main cause was exposure to inanimate mechanical forces (43.4% - 221). The most affected part of body was hand (51.1% - 260). Most workers evolved with temporary disabilities. Working conditions in rural areas demonstrated vulnerabilities in tlegal structure, in supervision of the use of hand tools and safe machinery, and in the correct and frequent access and use of personal protective equipment.